2012
DOI: 10.1262/jrd.2012-024
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Immunoreactivity of Vascular Endothelial Factor and its Receptors VEGFR1 and VEGFR2 in the Uterus of Wild Ground Squirrels (<i>Citellus dauricus</i> Brandt)

Abstract: Abstract. In this study, we investigated the immunoreactivity of vascular endothelial growth factor (VEGF) and its receptors flt-1 (VEGFR1) and the kinase domain receptor (KDR/Flk-1, VEGFR2) in the uteri of the wild ground squirrels during the estrous period, early pregnancy and nonbreeding period. Cellular localizations of VEGF, VEGFR1 and VEGFR2 were detected by immunohistochemistry, and total proteins were extracted from uterine tissue in the estrous period, early pregnancy and nonbreeding period for Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“… 32 , 33 Size and weight of reproductive organs were generally related to their reproductive ability. 34 The seasonality of uterine mass shown in the present study was in agreement with extensive reports in this species, 8 , 27 and the present histological results showed that the uterine gland grew bigger, including nucleus growth and gland lumen extension in the breeding season, and the gland lumen shrunk remarkably and less nuclei were observed in the non-breeding season. These findings were similar to those observations in other seasonal breeders, such as possums and dunnarts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 32 , 33 Size and weight of reproductive organs were generally related to their reproductive ability. 34 The seasonality of uterine mass shown in the present study was in agreement with extensive reports in this species, 8 , 27 and the present histological results showed that the uterine gland grew bigger, including nucleus growth and gland lumen extension in the breeding season, and the gland lumen shrunk remarkably and less nuclei were observed in the non-breeding season. These findings were similar to those observations in other seasonal breeders, such as possums and dunnarts.…”
Section: Discussionsupporting
confidence: 93%
“… 36 Our previous studies have also indicated that plasma estradiol-17β and progesterone concentrations were significantly higher in the breeding season than those in the non-breeding season in this species. 8 , 18 , 27 Therefore, the present results suggested that seasonal changes of uterine morphology and histology in the wild Daurian ground squirrels might be dependent on ovarian steroid hormones cycles.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The specificity of VEGF, VEGFR1 and VEGFR2 antibodies has been described in our previous studies. 28 Normal goat serum was selected to replace the initial antiserum treatment in the sections of the control group. The DAB staining was evaluated using ImageJ and the integrated density of positive staining area were calculated.…”
Section: Immunohistochemistrymentioning
confidence: 99%